(untitled) (Law and Safety, 2020)
The importance of the Minsk agreements in resolving the conflict and the fact that they are the only agreed basis for achieving peace in eastern Ukraine has been repeatedly stated by world leaders and leaders of international intergovernmental organizations (primarily the UN, OSCE, EU, NATO, etc.). This fact determines the high importance of the processes taking place in the field of peaceful resolution of the conflict in eastern Ukraine. The relevance of the chosen research topic is due to the fact that the process of resolving the military conflict in Ukraine in the context of establishing stable peace and security in the east, as well as returning the occupied territories of Donbass to Ukrainian control is given much attention by political leadership scientific environment and the average population. In addition, the implementation of the Minsk Agreements was discussed at various international official meetings at the highest political level with the participation of the Ukrainian side. For Ukraine, which in the framework of the «hybrid war» faced such factors as the temporary occupation of the territory of Ukraine by the Russian Federation, issues of peace and security in the east of the state have become extremely important. As a result, legal scholars are increasingly questioning the legal nature of the Minsk agreements themselves, as well as the nature of the parties’ international rights and obligations. The article examines the international legal aspects of clarifying the legal nature of the Minsk agreements. The parties’ different understanding of the Minsk agreements on their legal nature is analyzed, the possible legal consequences in case of non-compliance with these international legal documents are determined, and the role and place of the Minsk agreements in the process of peaceful settlement of the conflict in eastern Ukraine are clarified. Scientifically substantiated conclusions on the correct understanding and interpretation of the Minsk Agreements as a specific type of international legal documents are provided.